2000
DOI: 10.1159/000047315
|View full text |Cite
|
Sign up to set email alerts
|

Is the Morning Peak of Acute Myocardial Infarction’s Onset Due to Sleep-Related Breathing Disorders?

Abstract: Many studies have shown that the risk of experiencing a myocardial infarction (MI) is increased during the first hours of the morning. Sleep apnea syndrome (SAS) is associated with an enhanced adrenergic activity, prolonged a few hours after awakening. We aimed at assessing whether sleep breathing disorders could be a culprit for the morning excess rate of MI. We studied 40 middle-aged men admitted for an acute MI. An overnight polysomnographic study was performed 37.4 ± 9.4 days after the MI. The prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
1
15
0
1
Order By: Relevance
“…In a study reported by Aboyans et al, 10 no patient with sleep apnoea had MI between 0:00 and 5:59 hours. Only Kuniyoshi et al 8 examined the differences in circadian variation of MI onset between OSA and control patients.…”
Section: Discussionmentioning
confidence: 83%
“…In a study reported by Aboyans et al, 10 no patient with sleep apnoea had MI between 0:00 and 5:59 hours. Only Kuniyoshi et al 8 examined the differences in circadian variation of MI onset between OSA and control patients.…”
Section: Discussionmentioning
confidence: 83%
“…10 However, in a study that included 40 middle-aged men, the peak of MI onset was reported to be between 6 AM and 12 PM in those with SA. 11 …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] SDB was related with heart strain due to apnea and various cardiovascular diseases. Some studies have reported a relationship between SDB and myocardial ischemia, 2,[13][14][15] arrhythmia, [16][17][18] sudden death, 19) platelet coagulation, 20) and inflammatory cytokines, 21,22) all of which may trigger heart failure. These factors could therefore possibly cause heart failure between midnight and dawn.…”
Section: Discussionmentioning
confidence: 99%